1993
DOI: 10.1002/app.1993.070500903
|View full text |Cite
|
Sign up to set email alerts
|

Chain extension of recycled poly(ethylene terephthalate) with 2,2′‐Bis(2‐oxazoline)

Abstract: SYNOPSIS2,2'-Bis (2-oxazoline) was used as a chain extender during processing in a twin-screw extruder with the aim of counteracting degradation phenomena in recycled poly (ethylene terephthalate) (PET). The same experiments were performed on fiber-grade PET for comparison purposes. Rheological characterization showed that while the melt viscosity of fiber-grade PET at constant temperature and shear rate is quite constant with time, that of recycled P E T decreases dramatically. By addition of oxazoline, an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 36 publications
0
60
0
1
Order By: Relevance
“…These compounds reacted with the carboxyl or hydroxyl end groups of PET and resulted in chain-extended PET with very low carboxyl content. Cardi et al 27 confirmed the chain extension effect of 2,2Ј-bis(2-oxazoline) on recycled PET. Haralabakopoulos et al 28 showed that some commercially available cyclic diepoxides were effective in chain extension of PET.…”
Section: Introductionmentioning
confidence: 76%
“…These compounds reacted with the carboxyl or hydroxyl end groups of PET and resulted in chain-extended PET with very low carboxyl content. Cardi et al 27 confirmed the chain extension effect of 2,2Ј-bis(2-oxazoline) on recycled PET. Haralabakopoulos et al 28 showed that some commercially available cyclic diepoxides were effective in chain extension of PET.…”
Section: Introductionmentioning
confidence: 76%
“…These compounds reacted with the carboxyl or hydroxyl end group of PET and resulted in chain-extended PET with low carboxyl content. Cardi et al 27 confirmed the chain extension of recycled PET by adding 2,2-bis(2-oxazoline). Haralabakopoulos et al 28 showed that some commercially available cyclic diepoxides were effective in chain extension of PET.…”
Section: Introductionmentioning
confidence: 82%
“…The first class of contaminants is acids and acid-producing contaminants, for example, PVC, which produces hydrochloric acid [38,58]. Acids act as catalysts for chain cleavage reactions [59,60]. Similarly, elevated water content can lead to chain breakage through hydrolysis.…”
Section: Recyclingmentioning
confidence: 99%